Direct displacement based design of R/C structural walls - Bozer, Ali. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2003., 2003)
It is known that the conventional code based design has some drawbacks in estimating actual structure performance which stems from inconsistency between assumed force reduction factors and actual ductility demand as well as the utilization of gross section stiffness which ends up with significant errors in estimation of yield displacement. As a consequence, conventional code based designs are generally very conservative and actual structure performance is left unknown unless a more detailed analysis is performed. The object of this study is to review direct displacement based design methodology and to introduce an alternative approach for assessment of target displacement profile and effective damping ratio. This modified direct displacement based design enables one to design a structure for the selected performance level since the controlling design input is plastic hinge rotations which can be taken from ATC 40 for various performance levels. In this design methodology seismic design is performed by identifying a target displacement profile which is a function of plastic hinge rotation, section dimensions and reinforcement details used. Strength and stiffness are not the variables in the procedure but they are the end results. A series of moment-curvature and push over analyses were performed to verify design outputs for various structural wall sections. It is seen that the design plastic rotations as well as the target displacements are in conformity with the ones obtained from the analyses.
Keywords: Reinforced concrete construction.; Concrete walls -- Testing.